Pervasive m-Healthcare Framework for Diabetes - Gaur, Madhu Sharma; Pant, Bhasker (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*280.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922674);" role="presentation">Vision of pervasive computing includes wireless communication and information processing anywhere, anytime <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*291.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927115);" role="presentation">using mobile sensor devices connected seamlessly. Pervasive <span dir="ltr" style="left: calc(var(–scale-factor)*330.79px); top: calc(var(–scale-factor)*291.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.952484);" role="presentation">environment characterized by highly dynamic, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*303.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.919619);" role="presentation">open and diverse infrastructure where resource-<span dir="ltr" style="left: calc(var(–scale-factor)*267.65px); top: calc(var(–scale-factor)*303.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.96236);" role="presentation">restricted dissimilar mobile objects have the ability of Ad-<span dir="ltr" style="left: calc(var(–scale-factor)*509.02px); top: calc(var(–scale-factor)*303.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.894912);" role="presentation">hoc <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*314.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91779);" role="presentation">network set-<span dir="ltr" style="left: calc(var(–scale-factor)*122.18px); top: calc(var(–scale-factor)*314.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.935223);" role="presentation">up, self-<span dir="ltr" style="left: calc(var(–scale-factor)*155.42px); top: calc(var(–scale-factor)*314.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.927242);" role="presentation">organization and cooperation for information exchange and distributed operatio<span dir="ltr" style="left: calc(var(–scale-factor)*478.42px); top: calc(var(–scale-factor)*314.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.934603);" role="presentation">n unknown <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*326.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963859);" role="presentation">by the user. In such open computing environments, traditional security schemes and encryption algorithms <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*337.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.978706);" role="presentation">cannot be always applied to address the security assurance challenges. Therefore, concepts of trust and <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*349.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.94767);" role="presentation">reputation evaluation emerged by rese<span dir="ltr" style="left: calc(var(–scale-factor)*233.33px); top: calc(var(–scale-factor)*349.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.994997);" role="presentation">archers. In addition to that in human-<span dir="ltr" style="left: calc(var(–scale-factor)*394.99px); top: calc(var(–scale-factor)*349.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.93796);" role="presentation">centric healthcare applications, <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*360.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.963751);" role="presentation">reliability and trustworthiness between communicating nodes, quality of information assessment cannot be <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*372.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.920479);" role="presentation">effectively ensured through hard security concerns. Thus soft security analy<span dir="ltr" style="left: calc(var(–scale-factor)*378.55px); top: calc(var(–scale-factor)*372.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869966);" role="presentation">sis <span dir="ltr" style="left: calc(var(–scale-factor)*391.99px); top: calc(var(–scale-factor)*372.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.904288);" role="presentation">becomes an important aspect for <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*383.93px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.914104);" role="presentation">enhancing the security assurance and degree of trust in ICT enabled application and services where information <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*395.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908674);" role="presentation">is ubiquitous. In our proposed research work, we explore existing pervasive security and trust methods to assess <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*406.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.938165);" role="presentation">the challenging gap. We pu<span dir="ltr" style="left: calc(var(–scale-factor)*185.21px); top: calc(var(–scale-factor)*406.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.955837);" role="presentation">t forward need of soft security <span dir="ltr" style="left: calc(var(–scale-factor)*313.75px); top: calc(var(–scale-factor)*406.97px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931942);" role="presentation">and proposed a trust metric for trust based security <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.832967);" role="presentation">assessment <span dir="ltr" style="left: calc(var(–scale-factor)*122.52px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.999374);" role="presentation">with <span dir="ltr" style="left: calc(var(–scale-factor)*146.26px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898597);" role="presentation">classical <span dir="ltr" style="left: calc(var(–scale-factor)*186.20px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.924039);" role="presentation">clustering <span dir="ltr" style="left: calc(var(–scale-factor)*231.63px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.898936);" role="presentation">technique <span dir="ltr" style="left: calc(var(–scale-factor)*276.71px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">for <span dir="ltr" style="left: calc(var(–scale-factor)*294.43px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.891691);" role="presentation">energy-<span dir="ltr" style="left: calc(var(–scale-factor)*325.03px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.976168);" role="presentation">efficient <span dir="ltr" style="left: calc(var(–scale-factor)*360.91px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.871115);" role="presentation">resource <span dir="ltr" style="left: calc(var(–scale-factor)*400.81px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.908969);" role="presentation">restricted <span dir="ltr" style="left: calc(var(–scale-factor)*444.21px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.887768);" role="presentation">trusted <span dir="ltr" style="left: calc(var(–scale-factor)*477.41px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.86296);" role="presentation">and <span dir="ltr" style="left: calc(var(–scale-factor)*497.91px); top: calc(var(–scale-factor)*418.37px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.849765);" role="presentation">secure <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*429.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.968514);" role="presentation">communication. Major security attacks <span dir="ltr" style="left: calc(var(–scale-factor)*240.77px); top: calc(var(–scale-factor)*429.89px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.993581);" role="presentation">and impact of signal strength on security for unnoticed pervasive <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*441.41px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.974397);" role="presentation">services also evaluated. In winding up, we present pervasive healthcare application framework especially <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.888093);" role="presentation">focused <span dir="ltr" style="left: calc(var(–scale-factor)*106.82px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">to <span dir="ltr" style="left: calc(var(–scale-factor)*118.34px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.918944);" role="presentation">awareness and quality remote ca<span dir="ltr" style="left: calc(var(–scale-factor)*252.89px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.945752);" role="presentation">re for diabetes, to realize and <span dir="ltr" style="left: calc(var(–scale-factor)*378.91px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.996);" role="presentation">vali<span dir="ltr" style="left: calc(var(–scale-factor)*393.79px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.858337);" role="presentation">date <span dir="ltr" style="left: calc(var(–scale-factor)*414.19px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.931408);" role="presentation">th<span dir="ltr" style="left: calc(var(–scale-factor)*421.90px); top: calc(var(–scale-factor)*452.95px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.949588);" role="presentation">e conceptual model with <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*464.47px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.881254);" role="presentation">case study.